Determination of the Best Principles for Children in Divorce Cases: A Legal Analysis of the Cibinong Religious Court Decision Number 1042/Pdt.G/2019 - Halikha, Nazwa; Winanti, Atik (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
The purpose of this study is to determine the best principles for children in determining child custody, as well as to determine the legal considerations decided by the judge in determining child custody. This study is motivated by the number of divorce cases in Indonesia and the many children who become victims of conflict or parents. This study focuses on examining the best interests of children and legal considerations for judges in determining child custody arrangements due to divorce. This study uses a normative legal method with a case approach (Case Approach) and a statutory approach (Statute Approach), as well as library research data collection techniques. Custody is in line with the basic principles in Indonesian state regulations, namely the principle of the best interests of children. The results of this study indicate the provisions of Article 105 and Article 156 of the Compilation of Islamic Law. Article 105 of the Compilation of Islamic Law, explains that the provisions of the law on child custody which automatically grant custody to the mother, must be interpreted contextually. The main parameter that must be used as a reference is the best interests of the child. If the best interests of the child are not realized, then Article 105 of the Compilation of Islamic Law must be set aside and the judge must be guided by the best interests of the child. Although Article 105 of the Compilation of Islamic Law grants custody to the mother, the panel of judges also considers the father's ability and readiness to care for the child. The panel of judges decided to divide custody proportionally. For younger children, who still need intensive attention, custody is given to the mother. However, for older children, who are more emotionally stable, custody is given to the father. The panel of judges considered that this was the best solution to ensure the welfare of both children.